2020
DOI: 10.46265/genresj.2020.1.40-48
|View full text |Cite
|
Sign up to set email alerts
|

ECPGR recommended SSR loci for analyses of European plum (Prunus domestica) collections

Abstract: A set of nine Simple Sequence Repeat (SSR) loci, approved by the ECPGR Prunus working group, are proposed as a standard set for genotyping European plum accessions. These loci show sufficient reliability in spite of problems caused by hexaploidy. Polymorphism in the loci is high and enables differentiation between unique plum accessions as well as analyses of genetic grouping and overall genetic structure. A set of seven reference accessions are described. A compiled dataset with allelic information for 165 acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 37 publications
(50 reference statements)
2
15
0
Order By: Relevance
“…Hazelnut germplasm collections were analyzed in different world areas through biochemical [ 51 , 52 , 53 ], morphological, and genetic characterization using various molecular markers, among which SSRs are the most representative [ 28 , 34 , 38 , 54 ]. The development of molecular markers provided increasingly usable tools for DNA-based signature of tree crop varieties [ 55 , 56 , 57 ]. Here, nine SSR loci, standardized and recommended as replicable DNA-based markers by Biodiversity International [ 55 , 58 ], were employed to investigate the genetic diversity of Sicilian hazelnut germplasm cultivated in the Nebrodi Mountains, making possible the identification of varieties.…”
Section: Discussionmentioning
confidence: 99%
“…Hazelnut germplasm collections were analyzed in different world areas through biochemical [ 51 , 52 , 53 ], morphological, and genetic characterization using various molecular markers, among which SSRs are the most representative [ 28 , 34 , 38 , 54 ]. The development of molecular markers provided increasingly usable tools for DNA-based signature of tree crop varieties [ 55 , 56 , 57 ]. Here, nine SSR loci, standardized and recommended as replicable DNA-based markers by Biodiversity International [ 55 , 58 ], were employed to investigate the genetic diversity of Sicilian hazelnut germplasm cultivated in the Nebrodi Mountains, making possible the identification of varieties.…”
Section: Discussionmentioning
confidence: 99%
“…See Table 2 for diploid plum (P. salicina and related interspecific hybrids). The reference genotype is "Stanley" (from Nybom et al, 2020); (a) the REVERSE-PRIMER reported in Nybom et al (2020) for the marker UDP96-005 is not correct. For all SSR loci, the linkage group (LG) was reported in accordance with the GDR database and…”
Section: 36mentioning
confidence: 99%
“…Within these projects, morphological and genetic data were collected and analyzed on 104 accessions of local plums, conserved in 14 different European countries [49,86], and further extended to 165 accessions [87].…”
Section: Plum Varietal Diversitymentioning
confidence: 99%